Global analysis of mRNA decay intermediates in Bacillus subtilis wild-type and polynucleotide phosphorylase-deletion strains - Liu, Bo (2014)
Messenger RNA decay in Bacillus subtilis is accomplished by a combination of exoribonucleases and endoribonucleases. Intermediates in the decay process have not been readily detectable, and previous studies on mRNA decay have used a handful of highly expressed transcripts as models. Here, we use RNA-Seq analysis to probe mRNA turnover globally. A significant fraction of messages showed differential accumulation of RNA fragments that mapped near the 5’ or 3’ end of the coding sequence, consistent with initiation of decay from either the 5’ end or from an internal cleavage site. Patterns of mRNA decay in the wild type were compared with patterns in a mutant strain lacking polynucleotide phosphorylase (PNPase), which is considered the major 3’ exonuclease activity in mRNA decay and which is one of four known 3’ exonucleases in B. subtilis. The results showed a striking dependence on PNPase for mRNA turnover in many cases, suggesting specificity in the ability of 3’ exonucleases to degrade from 3’-hydroxyl termini. RNA-Seq data demonstrated a sharp decrease in expression of Sigma D in the PNPase-deletion strain. Reduction in sigD regulon expression explained the chain growth phenotype of the PNPase mutant and also predicted a defect in swarming motility.